Prognostic Value of Breast Cancer Subtypes, Ki‐67 Proliferation Index, Age, and Pathologic Tumor Characteristics on Breast Cancer Survival in Caucasian Women. Issue 1 (13th December 2012) - Ferguson, N. Lynn; Bell, John; Heidel, Robert; Lee, Solomon; VanMeter, Stuart; Duncan, Lisa; Munsey, Barbara; Panella, Timothy; Orucevic, Amila
Abstract Estrogen receptor (ER), progesterone receptor (PR), and epidermal growth factor receptor 2 (HER2) status are well‐established prognostic markers in breast cancer management. The triple negative breast carcinoma subtype (ER‐/PR‐/HER2‐) has been associated with worse overall prognosis in comparison with other subtypes in study populations consisting of ethnic minorities and young women. We evaluated the prognostic value of breast cancer subtypes, Ki‐67 proliferation index (Ki‐67PI), and pathologic tumor characteristics on breast cancer survival in Caucasian women in our institution, where greater than 90% of the total patient population is white. From 628 new invasive breast cancer cases in our data base (2000‐late 2004), 593 (94%) were identified in Caucasian women. ER/PR/HER2 breast cancer subtypes were classified based on St. Gallen International Expert Consensus recommendations from 2011. ER/PR/HER2 status and its effect on survival were analyzed using a Kaplan–Meier curve. ER/PR/HER2 status, grade, tumor‐node‐metastasis status (TNM)/anatomic stage, and age were analyzed in terms of survival in a multivariate fashion using a Cox regression. Ki‐67PI was analyzed between ER/PR/HER2 groups using the Kruskal–Wallis, Mann–Whitney U‐tests, and 2 × 5 ANOVA. Our results showed that patients with stage IIB through stage IV breast carcinomas were 2.1–16 times more likely to die than patients with stages IA‐B and IIA disease, respectively (95% CI 1.17–3.81 through 9.68–28.03, respectively), irrespective of ER/PR/HER2 subtype. Similar effect was seen with T2, N2/N3, or M1 tumors in comparison with T1, N0/N1, and M0 tumors. Chances of dying increase approximately 5% for every year increase in age. There was a significant main effect of Ki‐67PI between ER/PR/HER2 subtypes, p < .001, but Ki‐67PI could not predict survival. In summary, TNM status/anatomic stage of breast carcinomas and age are predictive of survival in our patient population of Caucasian women, but breast carcinoma subtypes and Ki‐67 proliferation index are not.